Evaluation of Public Satisfaction Levels With The Performance of Employees of The One-Stop Administrative System (Samsat) in Bengkulu City - Sudriyanti Putri (Penerbit Jurnal Indonesia, 2025)
Taxes are the main source of state revenue where state activities such as national development financed by taxes are difficult to carry out if there is no revenue from the tax sector. In the framework of the effectiveness of equitable development, decentralization from the central government to oversee and directly regulate affairs in the regions is urgently needed, so that policies, planning, implementation and financing are given to regional governments. The purpose of this study is to determine the influence of regulations and service quality on tax compliance for motor vehicle taxpayers. The method used in this research is explanatory research. Accidental sampling was used in this study by distributing questionnaires to 100 motorized vehicle taxpayers who were registered at Kantor Bersama Samsat of Bengkulu Province. The data analysis technique used is descriptive statisticalanalysis and multiple linear regression analysis. The results of this study indicate that the variables of knowledge and understanding of taxpayers about tax regulations and service quality have no significant effect on taxpayer compliance with motor vehicles registered at Kantor Bersama Samsat of Bengkulu Province.